Macroeconomic Outlook of the Philippines in 2023–2024: Prospects and Perils - Margarita Debuque-Gonzales; Mark Gerald C. Ruiz; Ramona Maria L. Miral (Philippine Institute for Development Studies (PIDS), 2023)
This paper, which will be released as the lead chapter of the 2022-2023 PIDS Economic Policy Monitor, examines the economic performance of the Philippines for 2022 and the first half of 2023. It presents conditions shaping the global and regional outlook, projections on growth and consumer prices, and prospects coming into 2024. Carried by post-pandemic momentum but moderated by continued headwinds, the economy grew by 7.6 percent in 2022. For 2023, GDP growth is expected to weaken to 5.2 percent, and inflation is estimated to average at about 6 percent. As for 2024, growth is anticipated to register between 5.5 to 6 percent, while inflation is expected to fall to the center of the target band. These projections consider the steady stream of income from abroad, an improved jobs picture, benign financial conditions, a less restrictive public budget, and a possible resurgence and/or rising business expectations in some sectors. On top of the issues listed in the previous edition, the current one draws attention to risks related to inflation, the country's fiscal position, and the newly created national investment fund.
Keywords: 330; Philippine economy; growth; inflation; forecast